If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(5x + -5) = -3 Reorder the terms: 4(-5 + 5x) = -3 (-5 * 4 + 5x * 4) = -3 (-20 + 20x) = -3 Solving -20 + 20x = -3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + 20x = -3 + 20 Combine like terms: -20 + 20 = 0 0 + 20x = -3 + 20 20x = -3 + 20 Combine like terms: -3 + 20 = 17 20x = 17 Divide each side by '20'. x = 0.85 Simplifying x = 0.85
| (x-3.2)(x-3/2)=0 | | x+(x-7)+3(x-7)=63 | | 6n+19=63 | | 2443=x*.0625 | | 6x-15=x+10 | | 8p=63 | | x+(x+7)+3(x+7)=63 | | 2(t-1)=32+2t | | -ab=-bc | | -(6a+8)-5(a-7)= | | x+(3x)+(x+7)=63 | | gf(x)=70 | | ax=-bc | | -9(1-2y)=18y-9 | | p-22=-30 | | -(3x+5)=6x | | -20-5+x=x | | (x^2)+400=625 | | B+5=3b+9 | | 7x+48=x+48 | | 0.3(9.9)= | | e-34=681 | | 7x-17=2x | | 9x-32=x-56 | | sin60=.5/x | | b-160=23 | | 6(x-72)-4(x+64)=64-6(x-72) | | 7x-36=x+24 | | 3x+2=4x+16 | | d=20(10) | | 5x+30=6x+26 | | 3x-2=6x+9 |